Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.pone.0084068
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Three RND Efflux Pumps in Doxycycline-Selected Strains of Burkholderia thailandensis

Abstract: BackgroundEfflux systems are involved in multidrug resistance in most Gram-negative non-fermentative bacteria. We have chosen Burkholderia thailandensis to dissect the development of multidrug resistance phenotypes under antibiotic pressure.Methodology/Principal FindingsWe used doxycycline selection to obtain several resistant B. thailandensis variants. The minimal inhibitory concentrations of a large panel of structurally unrelated antibiotics were determined ± the efflux pump inhibitor phenylalanine-arginine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…In E. coli, PA␤N at higher concentrations can inhibit efflux and destabilize outer membrane permeability (45); however, this phenomenon probably does not occur in B. pseudomallei due to the highest MICs being observed at the lowest PA␤N concentration, at least in the presence of gentamicin. Previous work in B. thailandensis has shown that the addition of PA␤N can upregulate amrB expression, which could potentially account for the increases in gentamicin MICs observed in this study (36). Caution should thus be taken when using efflux pump inhibitors, as they do not potentiate all antibiotic classes and can have the unintended consequence of increasing antibiotic resistance.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In E. coli, PA␤N at higher concentrations can inhibit efflux and destabilize outer membrane permeability (45); however, this phenomenon probably does not occur in B. pseudomallei due to the highest MICs being observed at the lowest PA␤N concentration, at least in the presence of gentamicin. Previous work in B. thailandensis has shown that the addition of PA␤N can upregulate amrB expression, which could potentially account for the increases in gentamicin MICs observed in this study (36). Caution should thus be taken when using efflux pump inhibitors, as they do not potentiate all antibiotic classes and can have the unintended consequence of increasing antibiotic resistance.…”
Section: Discussionmentioning
confidence: 74%
“…However, a recent publication reported that the presence of PA␤N at 50 and 100 g/ml decreased DOX resistance in B. pseudomallei under biofilm conditions (41). Similarly, reversion to a DOX-susceptible phenotype in the presence of PA␤N has been described in B. thailandensis (36). PA␤N has also been shown to have a competitive mechanism of inhibition in A. baumannii (42), P. aeruginosa (43), and E. coli (44).…”
Section: Discussionmentioning
confidence: 97%
“…When either of these pumps was inactivated, a third pump, BpeAB-OprB, was hyperexpressed, indicating the interplay among the three RND pumps (627), similar to those observed in P. aeruginosa (628) and Salmonella (629). Interestingly, an antagonistic effect between PA␤N (at 50 and 200 g/ml) and aminoglycosides/␤-lactams was observed, and the speculation was that PA␤N might have induced the overproduction of the AmrAB-OprA and BpeAB-OprB pumps (627). It remains to be determined whether an induction process exists for explaining the above-mentioned observations that PA␤N at 40 g/ml did not alter antibiotic susceptibility in B. pseudomallei (614,617) and that PA␤N at 20 g/ml did not affect the efflux activity of SmeDEF toward ciprofloxacin and tetracycline in S. maltophilia (630).…”
Section: Burkholderia Sppmentioning
confidence: 80%
“…Several more recent studies have also highlighted such OM-permeabilizing effects (974,975,1006,1007), although their conclusions need to be examined carefully, as discussed above (see Efflux Pump Inhibitors). In Burkholderia spp., PA␤N at a concentration of up to 200 g/ml was considered most effective as an EPI (627,1005). With this high level, its impact on OM permeability should be investigated.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation